Improved MSC Minimal Criteria to Maximize Patient Safety: A Call to Embrace Tissue Factor and Hemocompatibility Assessment of MSC Products - Moll, Guido; Ankrum, James A; Olson, Scott D; Nolta, Jan A (Stem cells translational medicine, 2022)
Abstract The number of mesenchymal stromal/stem cell (MSC) therapeutics and types of clinical applications have greatly diversified during the past decade, including rapid growth of poorly regulated “Stem Cell Clinics” offering diverse “Unproven Stem Cell Interventions.” This product diversification necessitates a critical evaluation of the reliance on the 2006 MSC minimal criteria to not only define MSC identity but characterize MSC suitability for intravascular administration. While high-quality MSC therapeutics have been safely administered intravascularly in well-controlled clinical trials, repeated case reports of mild-to-more-severe adverse events have been reported. These are most commonly related to thromboembolic complications upon infusion of highly procoagulant tissue factor (TF/CD142)-expressing MSC products. As TF/CD142 expression varies widely depending on the source and manufacturing process of the MSC product, additional clinical cell product characterization and guidelines are needed to ensure the safe use of MSC products. To minimize risk to patients receiving MSC therapy, we here propose to supplement the minimal criteria used for characterization of MSCs, to include criteria that assess the suitability of MSC products for intravascular use. If cell products are intended for intravascular delivery, which is true for half of all clinical applications involving MSCs, the effects of MSC on coagulation and hemocompatibility should be assessed and expression of TF/CD142 should be included as a phenotypic safety marker. This adjunct criterion will ensure both the identity of the MSCs as well as the safety of the MSCs has been vetted prior to intravascular delivery of MSC products. Graphical Abstract Graphical Abstract A broad spectrum of oversight impacts on MSC product safety in patients. We here outline the necessary steps toward integration of highly procoagulant tissue factor (TF/CD142) and hemocompatibility assessment of diversified intravascular MSC products as a new safety criterion into the existing MSC minimal criteria. Regulatory authorities and international societies should undertake coordinated efforts to update the already established guidelines.